THE UKRAINIAN FRONTIER AS A PULSING BOARDER SPACE OF EUROPE - Кисельов, Юрій (Human Geography Journal, 2014)
The issue of the Ukrainian frontier as a moving Eastern boarder of population and reclamation of the Eurasia’s geospace by Ukrainians is developed. The historical and geographical grounds for its shaping and the main stages of the frontier development are viewed. The staging of the Ukrainian frontier making is outlined. It is stressed that the Ukrainian frontier became an all-European one because of its extreme south-eastern localization in the European part of the continent. It is stressed on the geopolitical and geosophical role of the modern localization of the Ukrainian frontier in the Don River’s basin.